2018
DOI: 10.1159/000487890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Weight Loss Program on Metabolic Syndrome, Eating Disorders and Psychological Outcomes: Mediation by Endocannabinoids

Abstract: Objective: To evaluate the effects of weight loss on endocannabinoids, cardiometabolic and psychological parameters, eating disorders (ED) as well as quality of life (QoL) and to elucidate the role of endocannabinoids in metabolic syndrome (MS). Methods: In total, 114 patients with obesity were prospectively included in a 12-month weight loss program. Plasma endocannabinoids were measured by mass spectrometry; ED, psychological and QoL-related parameters were evaluated by self-reported questionnaires; physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
10
0
2
Order By: Relevance
“…While the animal data are not in agreement with the outcome of the current study, the ECS in animals may not necessarily be representative of the human ECS. PEA, in contrast, has been positively associated with total cholesterol and LDL cholesterol concentrations [47]. Interestingly, associations of PEA with HDL cholesterol were also positive in the current study whilst inverse associations were demonstrated previously [14].…”
Section: Discussionsupporting
confidence: 44%
“…While the animal data are not in agreement with the outcome of the current study, the ECS in animals may not necessarily be representative of the human ECS. PEA, in contrast, has been positively associated with total cholesterol and LDL cholesterol concentrations [47]. Interestingly, associations of PEA with HDL cholesterol were also positive in the current study whilst inverse associations were demonstrated previously [14].…”
Section: Discussionsupporting
confidence: 44%
“…They suggest a dual focus for weight loss interventions including weight loss strategies (lifestyle approaches, pharmacotherapy or surgery) and psychological well-being (evaluation and treatment of disordered eating symptoms) [ 48 ]. Pataky et al (2018) [ 49 ] showed that psychological parameters (e.g., eating, shape and weight concerns, disinhibition and self-esteem) can be improved in groups of participants that lost weight as well in groups that remained weight stable after 12 months of a multidisciplinary and lifestyle weight loss program. They hypothesized that the stabilization of weight can help the prevention of further weight gain during one year [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pataky et al (2018) [ 49 ] showed that psychological parameters (e.g., eating, shape and weight concerns, disinhibition and self-esteem) can be improved in groups of participants that lost weight as well in groups that remained weight stable after 12 months of a multidisciplinary and lifestyle weight loss program. They hypothesized that the stabilization of weight can help the prevention of further weight gain during one year [ 49 ]. It may be that weight stability can be as important as weight loss in some lifestyle respects for individuals with a high BMI receiving treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim, um programa multidisciplinar que envolva a atuação do psicólogo no processo de avaliação, comprometimento e desenvolvimento das habilidades emocionais, traz benefícios a saúde, melhoria na qualidade de vida e, consequentemente, a perda de peso. (Pataky et al, 2018) As avaliações psicológicas contribuem, não só para coletar dados e informações acerca das demandas e queixas dos Outro fator determinante encontrado dentro dos critérios estabelecidos é a pouca produção Brasileira de avaliação referente a essa temática, em comparação com as contribuições dos estudos internacionais. A diferença é expressiva, visto que Research, Society andDevelopment, v. 11, n. 1, e21111125038, 2022 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v11i1.25038 1 (um) estudo brasileiro foi selecionado, frente a 13 estudos internacionais.…”
Section: Discussionunclassified